Engendering transitional justice: a transformative approach to building peace and attaining human rights for women - Lambourne, Wendy (Human rights review, 2016)
In this article, we examine the continuity of harms and traumas experienced by women before, during and after war and other mass violence. We focus on women because of the particular challenges they face in accessing justice due to patriarchal structures and ongoing discrimination in the political, economic and social, as well as legal spheres, and because of the gendered nature of the crimes and harms they experience. We use the four key pillars of transitional justice identified by the United Nations as a framework to analyse how these harms are addressed in the context of criminal prosecutions, truth commissions, reparations and institutional reform. We conclude that a gender-transformative approach to transitional justice that focuses on transforming psychosocial, socioeconomic and political power relations in society is needed in order to attain human rights for women and build a sustainable peace.